(untitled) (Journal of the College of Education for Women, 2019)
Iben Katheer Al Dimashqi is considered among the eminent scholars in the eighth Hijri century / fourteenth Gregorian century. He acquired eminent academic and social standing. His book Albidaya Walnihaya is considered among the important historical sources. This book’s study of the subject of commercial dealing methods clarifies that the commercial dealing methods dealt by the people throughout the successive historical eras were multiple, most prominent of which was money (whether Dirhams, Dinars, measures (mikyals), weights (like Sa’) in addition to other means like usury. But here we notice that Iben Katheer stressed that usury must be prohibited because it is religiously forbidden and cited many Quranic verses and Prophetic sayings which confirm this. While there are other religiously permitted means, like mortgage and loans which solve a Muslim’s financial suffering. In addition to the existence of religiously permitted types of sales, like selling by choice, and forbidden types of sales, like betting sale and melting of fats and selling them which were restricted by the time of the Prophet Mohammed (Peace be upon him) where he prohibited those types of sales and forbid the Muslims from dealing by them.